'Presenting CXR phenotype of H1N1' flu compared with contemporaneous non-H1N1, community acquired pneumonia, during pandemic and post-pandemic outbreaks'. Issue 9 (September 2015) - Minns, F.C.; mhuineachain, A Ni; van Beek, E.J.R.; Ritchie, G.; Hill, A.; Murchison, J.T.
Highlights: Patients with H1N1 pneumonia demonstrated more opacified zones on chest x-ray than patients with non-H1N1 pneumonias. A particular 'phenotype' of chest x-ray changes was identified in H1N1 patients. This H1N1 'phenotype' was the same for the two evaluated 'flu seasons, during both pandemic and post pandemic stages. Abstract: Aims: To review, phenotype and assess potential prognostic value of initial chest X-ray findings in patients with H1N1 influenza during seasonal outbreaks of 2009 and 2010, in comparison with non-H1N1, community acquired pneumonia (CAP). Methods: We retrospectively identified 72 patients admitted to hospital with pneumonia during the seasons of 2009 and 2010. H1N1 cases were confirmed by virology PCR. Presenting chest X-rays were jointly read by 2 radiologists, who were 'blinded' to further patient details and divided into 6 zones. Total number of opacified zones, the pattern and distribution of changes and length of hospital stay were recorded. Results: Patients with H1N1 demonstrated more opacified zones (mean of 2.9 compared with 2.0; p  = 0.006), which were bilateral in two-thirds compared with a quarter of those with non-H1N1 CAP ( p  = 0.001). H1N1 radiographs were more likely to be 'patchy' versus 'confluent' changes of non-H1N1 CAP ( p  = 0.03) and more often demonstrated peripheral distribution ( p  = 0.01). H1N1 patients tended to stay in hospital longer (not significant; p  = 0.08). A positive correlation existed between number of affected zones and length of inpatient stay, which was statistically significant for the cohorts combined ( p  = 0.02). The findings were the same for the two evaluated seasons. Conclusion: H1N1 patients demonstrated more extensive disease, which was more likely bilateral, 'patchy', and peripheral in distribution. With increasing global cases of H1N1, knowledge of the typical findings of the H1N1 presenting chest X-ray may assist with early triage of patients, particularly where rapid viral testing is not available.